Consensus recommendations for the diagnosis and treatment of multiple sclerosis: the Middle East North Africa Committee for Treatment and Research In Multiple Sclerosis (MENACTRIMS). (July 2015) - Yamout, B.; Alroughani, R.; Al-Jumah, M.; Goueider, R.; Dahdaleh, M.; Inshasi, J.; Hashem, S.; Alsharoqi, I.; Sahraian, M.; Khoury, S.; Alkawi, Z.; Koussa, S.; et al.
Abstract With evolving diagnostic criteria and the advent of new oral and parenteral therapies for MS, most current diagnostic and treatment algorithms need re-evaluation and updating. The diagnosis of MS relies on incorporating clinical and paraclinical findings to prove dissemination in space and in time, and exclude alternative diseases that can explain the findings at hand. The differential diagnostic workup should be guided by clinical and laboratory red flags to avoid unnecessary tests. Appropriate multiple sclerosis (MS) therapy selection is critical to maximize patient benefit. The current guidelines review the scientific evidence supporting treatment of acute relapses, radiologically isolated syndrome, clinically isolated syndrome, relapsing remitting MS, secondary progressive MS, and primary progressive MS. The purpose of these guidelines is to provide practical recommendations and algorithms for the diagnosis and treatment of MS based on current scientific evidence and clinical experience.